Systematic review and meta-analysis of mean age at menarche in Iranian girls - Farideh Mohsenzadeh- ledari; Afsaneh Keramat; Ahmad Khosravi (Babol University of Medical Sciences, 2015)
Background: Many observational studies were published concerning the mean age at menarche and suggested those which may be a decreasing age at menarche in Iranian girls. The aim of this systematic review and meta-analysis was to estimate the overall mean age at menarche in Iranian girls.  Methods: We searched using online databases through December 2014 using and examined the reference lists of pertinent paper. Finally, 28 cross-sectional studies were selected for this meta-analysis. Cochran and tau-two tests were used for the detection of homogeneity of samples. The common average was calculated by random effect using RevMan 5 and Stata software. The cumulative meta-analysis and meta-regression were used to review the factors affecting heterogeneity.  Results: The mean age at menarche was13.9 years before 2000 and after 2000 was 12.6 years. The overall mean (95% CI) age at menarche was calculated 12.872 (95% CI: 12.874, 12.870) years based on stochastic models.  Conclusion: These findings indicated that the mean age at menarche in Iranian girls was less than that of the region and developing countries therefore performing a systematic review and meta-analysis to evaluate related factors that influence age at menarche in Iranian girls could be beneficial.